Development and validation of novel methods for the study of Staphylococcus aureus PVL strains - Otokunefor, Kome (2013)
Since the initial association of the Panton Valentine leucocidin (PVL) toxin with highly virulent strains of Staphylococcus aureus found in the community, a firm epidemiological link has been established between the PVL encoding genes and community-acquired strains of both meticillin resistant (CA-MRSA) and susceptible (CA-MSSA) Staphylococcus aureus. While most research has predominantly concentrated on the genotyping of CA-MRSA strains, PVL-MSSA appear to pose an increasing public health risk. Currently though, there exists a dearth of epidemiological data on PVL-MSSA strains, particularly with regard to the lukS and lukF genes which encode the PVL toxin.